Lamellar compact bone failure in tensile dynamic loading - Pithioux, Martine; Chabrand, Patrick (European Journal of Computational Mechanics, 2005)
Shock Biomechanics is a research domain mainly devoted to the development of safety conditions during locomotion and also in accidentology, or sport practices. The objective of this study is to improve the knowledge of the biomechanical behaviour of bones to sudden tensile dynamic loading. Femur and tibia are often broken during a shock, but actually, bones behaviours are studied in quasi-static but the failure caused by dynamic loading has not drawn the attention of many authors. Many of the tissues which constitute the lower limb, such as cartilage, ligaments and bones are fibrous. The objective of this work is to finely analyse the failure of a lamellar fibrous compact bone caused by a shock. The originality of this work is to describe failure in terms of the loss of cohesion between fibres of lamellar bone in dynamic loading. This model permits us to investigate the role plays by various parameters which influence failure of bones. Among them, bone porosity was found to be the most significant. In parallel, failure profiles of bovine compact bones are analysed experimentally in dynamic. Results were found to be comparable with our numerical model.